Experimentos de baixo custo e uso de tecnologias digitais da informação e comunicação (TDICs): proposta de aulas para ensino de mecânica, física térmica e eletromagnetismo - Cannavan, Marilin Celisa (Universidade Federal de São Carlos, 2021)
In this dissertation, three didactic sequences are proposed that take up some physics content with regular high school students (EM), aiming to prepare them for the National High School Exam (ENEM) and entrance exams. Starting from this reasoning, when structuring this research, we look for experiments built with low cost materials, with options for reusing parts found in everyday objects and of easy acquisition, these experiments involve in their functioning essential contents to be worked in High School, believing that these can awakening the students' interest. Other methodologies used in this work were: demonstration of simulations from the PhET Colorado website, work with small groups of students and videos. Care was taken to suggest methodologies that were accessible in various aspects for use in public schools. The pedagogical reference was the historical and cultural theory of Lev Semenovich Vygotsky, whose main point is the study of human development, under the influence of the environment in which the individual is inserted. The proposed classes were taught in a third-year high school class in October/2019, at a state school in the North Zone of the city of Sorocaba, with this group consisting of 43 students. However, it is worth mentioning that only 11 of them participated fully in the activities (they did not miss any of the days of the application of the classes and signed all the authorization terms to participate in the research), for this reason, we consider the data of the evaluations of these 11 students. The application of the product was divided into three stages with four classes of fifty minutes each, totaling 12 classes for the entire process. The topics covered in each of the stages were: Mechanics - Energies, Thermal Physics and Electromagnetism. For each stage, an experiment was proposed that collaborated with the learning of the concepts covered in the classes, which are: cardboard roller coaster, thermoelectric mini generator and electromagnetic induction generator.
Low-cost experiments and the use of digital information and communication technologies (DICTs): class proposals for teaching mechanics, thermal physics and electromagnetism.
Keywords: Ensino de Física; Demonstração Experimental; Teoria Histórico-Cultural do Desenvolvimento; Teaching Physics; Experimental Demonstration; Historical-Cultural Development Theory; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA GERAL